2021
DOI: 10.1002/cbin.11574
|View full text |Cite
|
Sign up to set email alerts
|

RACK1 mediates the advanced glycation end product‐induced degradation of HIF‐1α in nucleus pulposus cells via competing with HSP90 for HIF‐1α binding

Abstract: Hyperglycemia can drive advanced glycation end product (AGE) accumulation and associated nucleus pulposus cell (NPC) dysfunction, but the basis for this activity has not been elucidated. Hypoxia‐inducible factor‐1α (HIF‐1α) is subject to cell‐type‐specific AGE‐mediated regulation. In the current study, we assessed the mechanistic relationship between AGE accumulation and HIF‐1α degradation in NPCs. Immunohistochemical staining of degenerated nucleus pulposus (NP) samples was used to assess AGE levels. AGE impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…In studies on nucleus pulposus cell dysfunction, HSP90 was shown to help stabilize HIF-1α in normoxia. 55 In our study, after blocking the binding of HSP90 to HIF-1α, glycolysis became weaker, and ATP, NADPH, and GSH levels decreased, while ROS levels increased markedly. These results demonstrate that the MTNR1B-HSP90-HIF-1α axis is essential to melatonin reprogramming in glucose metabolism and to attenuate heat stress-induced injury in SCs (Figure 8).…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…In studies on nucleus pulposus cell dysfunction, HSP90 was shown to help stabilize HIF-1α in normoxia. 55 In our study, after blocking the binding of HSP90 to HIF-1α, glycolysis became weaker, and ATP, NADPH, and GSH levels decreased, while ROS levels increased markedly. These results demonstrate that the MTNR1B-HSP90-HIF-1α axis is essential to melatonin reprogramming in glucose metabolism and to attenuate heat stress-induced injury in SCs (Figure 8).…”
Section: Discussionsupporting
confidence: 46%
“…However, under normoxic conditions, HIF‐1α is commonly degraded. In studies on nucleus pulposus cell dysfunction, HSP90 was shown to help stabilize HIF‐1α in normoxia 55 . In our study, after blocking the binding of HSP90 to HIF‐1α, glycolysis became weaker, and ATP, NADPH, and GSH levels decreased, while ROS levels increased markedly.…”
Section: Discussionmentioning
confidence: 50%
“…31 The high concentrations of blood glucose in the physiological environment not only reduce the bioactivity of vascular endothelial growth factor (VEGF) and hypoxia-inducible factor 1α (HIF-1α) but also induce the non-enzymatic glycosylation reaction of biological macromolecules, further resulting in advanced glycation end products. 32 The resulting products will decrease the hydrophilicity of the extracellular matrix, further making a diabetic wound chronically remained inflamed. 33…”
Section: Hyperglycemiamentioning
confidence: 99%
“…Following AGEs treatment, the receptor for activated C-kinase 1 (RACK1) competes with heat shock protein 90 (HSP90) for binding to HIF-1 α , resulting in posttranslational HIF-1 α degradation and RACK1-mediated proteasomal degradation, independently of the canonical iron-dependent prolyl-hydroxylase domain- (PHD-) mediated degradation pathway. Under normoxic conditions, PHD proteins promote HIF-1 α degradation by the 26S proteasome [ 76 , 77 ]. The degradation of HIF-1 α disrupts the biological function of NP cells and promotes IDD.…”
Section: Effect Of Ages On Ivdmentioning
confidence: 99%